2022
DOI: 10.1016/j.heliyon.2022.e08825
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics self-medication practices among health care professionals in selected public hospitals of Addis Ababa, Ethiopia

Abstract: Background: Self-medication is the first option and response to most illness episodes. Use of antimicrobials without health care professionals' guidance may result in greater probability of inappropriate use, missed diagnosis, delays in appropriate treatment, pathogen resistance and increased morbidity. There is no sector in the health care community which is immune to drug abuse or misuse of which the worst offenders include physicians, nurses and pharmacy professionals. Self-medication among health care prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
(57 reference statements)
2
9
1
Order By: Relevance
“…In addition, this was also the case among HCWs in Nigeria (54.6–89.3%) [ 104 , 112 ]. However, this is in contrast to another study in Nigeria, where only one third of HCWs surveyed practiced self-medication during the COVID-19 pandemic [ 64 ], and in Ethiopia (22.7%) [ 113 ], with similar findings among pooled studies of HCWs across multiple countries (32.5%) [ 111 ].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In addition, this was also the case among HCWs in Nigeria (54.6–89.3%) [ 104 , 112 ]. However, this is in contrast to another study in Nigeria, where only one third of HCWs surveyed practiced self-medication during the COVID-19 pandemic [ 64 ], and in Ethiopia (22.7%) [ 113 ], with similar findings among pooled studies of HCWs across multiple countries (32.5%) [ 111 ].…”
Section: Discussioncontrasting
confidence: 70%
“…The data collection tool used in our survey was developed from previous studies combined with the considerable experience of the co-authors as well as observing local practices [ 55 , 103 , 110 , 113 , 114 , 139 ]. We have used this method before when developing context-specific data collection forms [ 101 , 131 , 140 , 141 , 142 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar to our results, a study by Jorgji et al [11] reported that 78.14% of the participants had received antibiotics without a medical prescription. Compared to the prevalence of selfmedication with antibiotics among health care provider, a current Ethiopian study had reported it in a one-month recall period to be (22.7%), and they stated that the main reason "given for this practice was being familiar with the treatment options" [12]. The current study found that 18.9% stopped the antibiotics upon completion of the course (treatment course), while 32.8% stopped the antibiotics after symptoms disappear, 13.8% after a few days of recovery, while El Zowalaty et al reported that 71.1 % did not finish the antibiotic course as they felt better [10].…”
Section: Discussionmentioning
confidence: 95%
“…A few studies have been undertaken in Ethiopia to investigate the usage of self-medication among the public and students, including medical students [ 27 – 29 ], and there are indications on the misuse of antibiotics by patients, even by health professionals [ 30 ]. However, there is no study conducted on self-medication practice with antibiotics of adult outpatients in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%